Local community participation in coastal zone management in Port Klang, Selangor - Asmawi, M. Zainora (International Islamic University Malaysia, 2010)
There is a growing recognition of the value and benefits of working at the community level. It is at the local level that much of the real-action in coastal zone management is taking place. As such, the proposed research will examine about the importance of community participation in coastal zone management initiative, namely Port Klang Coastal Strategy. Issues related to the balance between providing for meaningful community participation and achieving coastal management objectives are expected to consider. This study also expects to determine the possible reasons why community participation has a relatively low profile in Malaysian coastal management initiatives.